Analysis of cu and NI concentrations in some commonly consumed spices sold in Kaduna metropolis, Kaduna state, Nigeria - J, Omenesa; Y, Mohammed; A.O, Babatunde; S.J, Salawu (International Journal of Advanced Chemistry, 2023)
This research was conducted with a view to determine the risks associated with Cu, and Ni through the consumption of spices viz; curry leaves, ginger, turmeric, garlic and cloves) sold within Kaduna Metropolis. The samples were analyzed for Cu and Ni using Atomic Absorption Spectrophotometer (AAS). The mean concentrations of the metals in the samples are curry leaves: - Cu (0.123 mg/kg); Ni (0.029 mg/kg). Ginger:- Cu (0.063 mg/kg); Ni (0.046 mg/kg). Garlic: - Cu (0.064 mg/kg); Ni (0.034 mg/kg). Cloves: - Cu (0.056 mg/kg); Ni (0.024 mg/kg). Turmeric: - Cu (0.052 mg/kg); Ni (0.022 mg/kg). The concentration of Cu and Ni analyzed in all the samples are within the safety limits set by FAO/WHO while the Target Hazard Quotient (THQ) evaluated for all the samples were less than one (1). Hence, the selected spices sold within Kaduna Metropolis are safe for human consumption.